Dasar Program Perencanaan Dan Perancangan Arsitektur(DP3A) Tanjung Emas Container Apartment - IKHSANUDIN, KHABIB, Ir. Nurhasan, MT (2017)
Tanjung Emas Container Apartment is a vertical housing who use material container as an alternative building material that located within the industry the Tanjung Emas port of Semarang. Tanjung Emas port of Semarang had a role as a transport hub of the scale of local until an international scale. It causes the awareness that the existence of labor having a very important role in activities port. So that the large number of labor can make the impact increase public need live or occupancy. In addition the existence of the port have also will invite the community to settle down in their surroundings port that will lead to the dense settlement located within the port. This can be seen from the increase in the port in the environment every year. The existence of Tanjung Emas Container Apartment, besides as a dwelling or dwelling, also is expected to be a space social, economic as well as education for people with various the profession located within the port.